THE USE OF VIDEO CONFERENCE FOR SPEAKING CLASS IN SHIP ELECTRICAL ENGINEERING OF IVET UNIVERSITY FOCUS ON PRACTICES AND PERCEPTION - Wibowo, Rachmat Ari; Sulistyorini, Dwi (JURNAL SAINS DAN TEKNOLOGI MARITIM, 2024)
One of the core subjects that has been considered for all generations is English. Being able to converse inEnglish is one of the main objectives of the language. Speaking requires the active production of language,making it a productive talent (Baker, 2003). Cadets are taught appropriate speech during English languageinstruction so they can communicate effectively. The cadets' ability to complete the given language activity andunderstand the speaking competency constitutes success in speaking English. As a result, the video conferenceimplementation for the Speaking for Formal Interactions course at Ivet University's third-semester cadets inShip Electrical Engineering has gone off without a hitch. Utilizing different techniques, plans of action, and extra supporting systems like Quizizz, WhatsApp Groups, Zoom Meetings, and others helps withimplementation. Speaking professors and cadets also mostly benefit from video conferences in terms ofefficacy, ease of connection, technology, and cost rather than experiencing any drawbacks In order to collect thedata, a number of approaches, including observation, interviewing, and a questionnaire, were employed tocollect the data. The human instrument, observation sheet, questionnaire, and interview guide were study toolsat the same time. A technique from Miles and Hubberman (1991) was used to analyze the data that had beengathered. Additionally, the current study used methodological triangulation, which is the use of multiple data-collection techniques, including observation, interview, and questionnaire. In addition to using videoconferencing for speaking, the attitudes of the lecturers and the cadets regarding using video conferencing forSpeaking for Formal Interactions were also examined. The 15 items in the questionnaire were divided into fourcategories based on factors including video conferencing efficacy, accessibility, cost, and technology.